In vitro activity of alpha-viniferin isolated from the roots of Carex humilis against Mycobacterium tuberculosis. (October 2017) - Seo, Hoonhee; Kim, Mijung; Kim, Sukyung; Mahmud, Hafij Al; Islam, Md Imtiazul; Nam, Kung-Woo; Cho, Myoung-Lae; Kwon, Hyun-Sook; Song, Ho-Yeon
Abstract: This study explores the antitubercular activity of α-viniferin, a bioactive phytochemical compound obtained from Carex humilis . α-Viniferin was active against both drug-susceptible and -resistant strains of Mycobacterium tuberculosis at MIC50 s of 4.6 μM in culture broth medium and MIC50 s of 2.3–4.6 μM inside macrophages and pneumocytes. In combination with streptomycin and ethambutol, α-viniferin exhibited an additive effect and partial synergy, respectively, against M. tuberculosis H37Rv. α-Viniferin also did not show cytotoxicity in any of the cell lines tested up to a concentration of 147 μM, which gives this compound a selectivity index of >32. Moreover, α-viniferin was active against 3 Staphylococcus species, including methicillin-susceptible Staphylococcus aureus (MSSA), methicillin-resistant Staphylococcus aureus (MRSA), and methicillin-resistant Staphylococcus epidermidis (MRSE).